Overcoming drug resistance in HSV, CMV, HBV and HCV infection. (November 2015) - López-Labrador, F. Xavier; Berenguer, Marina; Navarro, David
Although vaccination has provided as a very efficient preventive tool, antiviral therapy is still needed to control viral infections not avoidable by prophylaxis with vaccines; those caused by viruses for which a vaccine is available, but vaccination is not universally implemented or does not result in complete, long-term protection; and in immunocompromised individuals with reduced immune control of viral replication. After more than 50 years of the first licensing for an antiherpetic drug, novel compounds for herpes-simplex viruses and human cytomegalovirus will open new strategies for better control and management of these two recurrent viral infections. Besides, the development and use of antiviral drugs for hepatitis viruses causing chronic liver disease has evolved from the unavailability of compounds targeting virus-specific pathways, to the generalization of different treatment regimes based on specific antiviral drugs, both for hepatitis B and C viruses. However, due to the nature of the viral genomes and their replication, in the face of the selective pressure imposed by antiviral drugs viral-resistant variants inevitably emerge, and specific strategies are needed to avoid, or reduce, their clinical and public health impact.